A photolithography coating process capable of controlling coating thickness for producing quartz substrate

By adopting a two-layer glue coating process on the quartz substrate, combined with variable speed uniform glue and exhaust pressure thickness control technology, the problem of difficult to control the film thickness during the glue coating process is solved, and the precise control of the film thickness and the flatness of the overall surface are achieved.

CN117369214BActive Publication Date: 2025-03-04ANHUI HECHEN NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311552221.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-03-04
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

In the prior art, the thickness of the adhesive film is difficult to control during the glue coating process of quartz substrate, resulting in a large film thickness error and affecting subsequent processing.

Method used

The two-layer glue coating process is adopted. The first layer of glue film controls the thickness through the first and second stage variable speed uniform glue process to ensure that it is within the set range. Then, the second layer of glue film is applied on the basis of it, and the thickness is controlled by exhaust pressure to ensure that the overall surface is flat.

Benefits of technology

The precise control of the thickness of the quartz substrate coating is achieved, and the film thickness error is within 5%, ensuring the uniformity and flatness of the entire film layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117369214B_ABST
    Figure CN117369214B_ABST
Patent Text Reader

Abstract

The present invention discloses a photoresist coating process with controllable coating thickness for quartz substrate production, belonging to the field of photoresist coating technology. A photoresist coating process with controllable coating thickness for quartz substrate production includes the following steps: S1: pre-treating the quartz substrate and adsorbing it onto a vacuum suction cup; S2: controlling the rotation of the quartz substrate, dripping photoresist to the center of the quartz substrate, and rotating it in a variable speed manner within a set time period. The present invention coats the quartz substrate twice. In the first coating, the first stage variable speed coating is adopted, which can quickly flatten the photoresist on the quartz substrate, and prevent the appearance of reticulation on the edge of the quartz substrate, thereby ensuring the flatness and uniformity of the first layer of the quartz substrate film, and using an infrared micrometer to detect the thickness of the first layer of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photolithography glue coating, in particular to a photolithography glue coating process capable of controlling glue coating thickness for producing quartz substrates. Background Art

[0002] In the semiconductor manufacturing process, metal patterns are usually used to make device leads and electrodes. These metal patterns are usually formed by photolithography followed by wet or dry etching. However, some metals are difficult to etch using wet or dry etching, and the chemicals required to etch these metal patterns will have a corrosive effect on other parts of the semiconductor device. Therefore, a lift-off process is usually used to make these metal patterns.

[0003] The Chinese patent with publication number CN115793397A discloses a high-precision quartz substrate coating and its production process. In the material for preparing the first adhesive layer, a high-temperature resistant silicone resin material is added, which is resistant to high temperatures and impacts. When the second adhesive layer is pressurized, the first adhesive layer is not easily deformed, thereby achieving an inverted T-shaped coating pattern. The application does not control the thickness of the adhesive film during the coating process, and the error of the film thickness is large, which has a great impact on subsequent processing. Summary of the invention

[0004] The purpose of the present invention is to provide a photolithography coating process with controllable coating thickness for quartz substrate production. By ensuring that the thickness of the first layer of film is within a set range, a second layer of film is coated on the basis of the first layer of film, so that the overall surface is smoother, thereby achieving uniformity of the entire film layer, and solving the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a photolithography coating process with controllable coating thickness for producing a quartz substrate, comprising the following steps:

[0006] S1: The quartz substrate is pre-treated and adsorbed onto the vacuum chuck;

[0007] S2: Control the rotation of the quartz substrate, drip photoresist to the center of the quartz substrate, rotate it at a variable speed within a set time period, measure whether the film thickness is within the set range, clean the back side and dry it;

[0008] S3: The quartz substrate is adsorbed onto the vacuum chuck again, and photoresist is dripped onto the center of the quartz substrate. The substrate is first rotated at the first speed and then at the second speed. The thickness is controlled by exhaust pressure. The back side is cleaned and then dried.

[0009] Preferably, the pretreatment process of the quartz substrate in S1 is as follows: the quartz substrate to be coated with glue is cleaned, the cleaning water is blown off, and then it is dried to check whether there is any water mark, the quartz substrate is adsorbed onto a vacuum suction cup, a diluent is dripped onto the quartz substrate, and it is shaken evenly.

[0010] Preferably, the specific steps of S2 are as follows:

[0011] S21: controlling the quartz substrate to accelerate to 1000 rpm within 1 second, dripping photoresist onto the quartz substrate, using the first stage variable speed coating, and detecting the thickness of the first film at the same time;

[0012] S22: using the second stage variable speed glue leveling to detect the thickness of the first glue film and control the thickness of the glue film to within a set range;

[0013] S23: The rotation speed is controlled to drop to 1000 rpm, maintained for 15 seconds, and then dropped to a stationary state. During the process, the quartz substrate is washed on the edge and the back, and the quartz substrate is placed in an oven at 90° C. for 20 minutes.

[0014] Preferably, the specific process of the first stage of variable speed glue spreading is as follows: first accelerate to 4500rpm, maintain for 5s, decelerate to 3000rpm within 1s, maintain for 5s, and at the speed of 3000rpm, detect the first layer of glue film on the quartz substrate. If the error range of the film thickness is outside 25% with the set film thickness, perform the previous acceleration and deceleration again. If the error range of the film thickness is within 25% with the set film thickness, enter the second stage of variable speed glue spreading.

[0015] Preferably, the specific process of the second stage of speed-changing glue spreading is as follows: accelerate to the set speed within 1s, maintain for 5s, slow down to 3000rpm, maintain for 5s, and then perform 1-4 times of acceleration to the set speed and deceleration to 3000rpm. When the speed is 3000rpm, the thickness of the first layer of glue film on the quartz substrate is detected. When the error range between the detected film thickness and the set film thickness is within 5%, the second stage speed change is stopped.

[0016] Preferably, the set speed is calculated based on the detected thickness of the first layer of film, and the calculation formula for the set speed is: V2=3000(T1·T1) / (T2·T2), wherein V2 is the set speed, T1 is the current film thickness, and T2 is the set film thickness.

[0017] Preferably, the specific steps of S3 are as follows:

[0018] S31: dripping photoresist to the center of the quartz substrate, accelerating to the first speed within 3 seconds, and maintaining for 10 seconds. During the process, exhausting air vertically to the dripping range of the quartz substrate;

[0019] S32: accelerating to the second speed within 3 seconds, during which the entire upper surface of the quartz substrate is vertically and evenly exhausted, and the thickness of the second layer of film on the quartz substrate is monitored at the same time;

[0020] S33: When the thickness of the second layer of film on the quartz substrate reaches the set value, the rotation speed is controlled to drop to 1000 rpm, maintained for 15 seconds and then dropped to a stationary state. During the process, the quartz substrate is washed on the edge and the back, and the quartz substrate is placed in an oven at 100°C for 25 minutes.

[0021] Preferably, the first speed is 2000 rpm and the second speed is 3000 rpm.

[0022] Preferably, the exhaust pressure is 100Pa-120Pa.

[0023] Preferably, the thickness of the first layer of adhesive film and the second layer of adhesive film are detected by an infrared micrometer.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The quartz substrate is coated with glue twice. In the first coating, the first stage variable speed glue leveling is adopted to quickly level the photoresist on the quartz substrate and prevent the appearance of reticulation on the edge of the quartz substrate, thereby ensuring the flatness and uniformity of the first layer of glue film on the quartz substrate. The thickness of the first layer of glue film is detected by an infrared micrometer, and the rotation speed is calculated and set according to the detected thickness of the first layer of glue film. The speed is adjusted for different quartz substrates in a targeted manner to ensure that the error range of the film thickness is within 5%. When the thickness of the first layer of glue film is ensured to be within the set range, the second layer of glue film is coated on the basis of the first layer of glue film. The glue leveling speed of the second layer of glue film is slower. At this time, the second layer of glue film is pressurized with an air pressure of 100Pa-120Pa to ensure that the overall surface is smoother on the basis of the thick film layer, thereby achieving the uniformity of the entire film layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a measurement curve diagram of the thickness distribution of the first layer of adhesive film of the present invention;

[0027] Figure 2 is a measurement curve diagram of the thickness distribution of the second layer of the adhesive film of the present invention;

[0028] Figure 3 It is a measurement curve diagram of the total film thickness distribution of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In order to solve the problem that the thickness of the adhesive film cannot be controlled during the existing coating process, the error of the film thickness is large, and the subsequent processing has a great impact, this embodiment provides the following technical solutions:

[0031] A photolithography coating process capable of controlling the coating thickness for producing a quartz substrate comprises the following steps:

[0032] S1: Take a Φ50mm quartz plate for pretreatment and adsorb it onto a vacuum suction cup. Specifically, clean the quartz substrate to be coated with glue, blow dry the cleaning water, dry it, check that there is no water mark, adsorb the quartz substrate onto the vacuum suction cup, add a diluent to the quartz substrate, and shake it evenly. The diluent is propylene glycol methyl ether acetate, the amount of addition is 5ml, the shaking time is 10-20s, and the rotation speed is 2000-3000rpm.

[0033] S2: Control the rotation of the quartz substrate, drip photoresist to the center of the quartz substrate, rotate it at a variable speed within a set time period, measure whether the film thickness is within the set range, clean the back side and dry it.

[0034] The specific steps are as follows:

[0035] S21: Control the quartz substrate to accelerate to 1000rpm within 1s, drip photoresist onto the quartz substrate, adopt the first stage of variable speed glue spreading, and detect the thickness of the first glue film at the same time; the specific process of the first stage of variable speed glue spreading is as follows: first accelerate to 4500rpm, maintain for 5s, quickly spread the photoresist on the quartz substrate, and throw the excess photoresist off the surface of the quartz substrate, decelerate to 3000rpm within 1s, maintain for 5s, reduce the speed to prevent the edge of the quartz substrate from appearing mesh when rotating too fast, and detect the first layer of glue film on the quartz substrate at a speed of 3000rpm. If the error range of the film thickness is outside 25%, perform the previous acceleration and deceleration again. If the error range of the film thickness is within 25%, enter the second stage of variable speed glue spreading. By detecting the film thickness, it is determined whether it is necessary to enter the next process. In the first stage of variable speed glue spreading, it mainly serves the purpose of roughly controlling the glue thickness and narrowing the control range.

[0036] S22: Use the second stage variable speed glue leveling to detect the thickness of the first glue film and control the glue film thickness to within the set range; the specific process of the second stage variable speed glue leveling is as follows: accelerate to the set speed within 1s and maintain for 5s. The set speed is calculated according to the current glue film thickness, that is, the set speed is automatically adjusted according to the existing thickness, which can better realize the influence of the speed on the glue coating thickness, and the speed is reduced to 3000rpm and maintained for 5s. Maintaining a high speed for a long time is prone to thinning too quickly. The speed is appropriately reduced to gradually control the thinning of the film layer. In this way, 1-4 times of acceleration to the set speed and deceleration to 3000rpm are performed. The specific number of times depends on the thickness detection result. When the speed is 3000rpm, the thickness of the first layer of glue film on the quartz substrate is detected. When the error range between the detected film thickness and the set film thickness is within 5%, the second stage speed change is stopped. 5% is the allowable error of the film thickness.

[0037] The set speed is calculated based on the detected thickness of the first layer of film. The calculation formula for the set speed is: V2=3000(T1·T1) / (T2·T2), where V2 is the set speed, T1 is the current film thickness, and T2 is the set film thickness. The thickness of the first layer of film is detected by an infrared micrometer.

[0038] S23: The rotation speed is controlled to drop to 1000 rpm, maintained for 15 seconds, and then dropped to a stationary state. During the process, the quartz substrate is washed at the edge and the back, and the excess colloid on the edge and the back of the quartz substrate is cleaned. The quartz substrate is placed in an oven at 90° C. and baked for 20 minutes.

[0039] S3: The quartz substrate is adsorbed onto the vacuum chuck again, photoresist is dripped onto the center of the quartz substrate, it is rotated at the first speed first, then at the second speed, the exhaust pressure is used to control the thickness, the back side is cleaned and then dried. The specific steps are as follows:

[0040] S31: dripping photoresist to the center of the quartz substrate, accelerating to the first speed within 3 seconds, the first speed is 2000rpm, and maintained for 10 seconds. This speed is slower than the glue-spreading speed of the first layer of glue film, and can retain more glue on the surface of the quartz substrate. The thickness of the prepared second layer of glue film is thicker than the first layer of glue film. During the process, the glue dripping range of the quartz substrate is vertically exhausted, and the exhaust pressure is 100Pa-120Pa. Through the exhaust, pressure is applied to the photoresist surface, and then the dripped photoresist is pushed from the center to the edge of the quartz substrate to prevent the glue film in the middle of the quartz substrate from being too thick;

[0041] S32: Accelerate to the second speed within 3s, the second speed is 3000rpm. During the process, exhaust gas is vertically and evenly discharged to the entire upper surface of the quartz substrate. The exhaust gas pressure is 100Pa-120Pa. The uniform overall pressure can accelerate the thinning of the second layer of film. Different from using only centrifugal force, the longitudinal pressure is increased, which can squeeze the protruding position of the second layer of film toward the concave position, thereby improving the uniformity of the second layer of film. At the same time, the thickness of the second layer of film on the quartz substrate is monitored. The thickness of the second layer of film is detected by an infrared micrometer.

[0042] S33: When the thickness of the second layer of film on the quartz substrate reaches the set value, the rotation speed is controlled to drop to 1000 rpm, maintained for 15 seconds and then dropped to a stationary state. During the process, the quartz substrate is washed on the edge and the back, and the quartz substrate is placed in an oven at 100°C for 25 minutes.

[0043] Embodiment 1:

[0044] Take a Φ50mm quartz plate and use the above process to perform glue leveling. Set the thickness of the first layer of glue film to 1um, the thickness of the second layer of glue film to 2um, and the allowable error to be 5%. When leveling glue for the first time, add 5ml of photoresist, first accelerate to 4500rpm, keep for 5s, reduce the speed to 3000rpm within 1s, and keep for 5s. The thickness of the first layer of glue film on the quartz substrate is detected to be 1.13um. Accelerate to 3831rpm within 1s, keep for 5s, reduce the speed to 3000rpm within 1s, and detect The thickness of the first layer of film on the quartz substrate was 1.08um. It was accelerated to 3499rpm within 1s, maintained for 5s, and then reduced to 3000rpm within 1s. The thickness of the first layer of film on the quartz substrate was detected to be 1.03um. The speed was controlled to drop to 1000rpm, maintained for 15s and then dropped to a stationary state. During the process, the quartz substrate was washed on the edge and the back, and the quartz substrate was placed in an oven at 90°C for 20min. After drying to room temperature, the average thickness of the first layer of film was detected to be 0.99um.

[0045] When the second glue was spread, 5 ml of photoresist was added, and the speed was accelerated to 2000 rpm within 3 seconds and maintained for 10 seconds. During the process, the quartz substrate was exhausted vertically to the glue dripping range, and the exhaust pressure was 100 Pa. The speed was accelerated to 3000 rpm within 3 seconds, and the exhaust was vertically and evenly conducted to the entire upper surface of the quartz substrate, and the exhaust pressure was 100 Pa. When it was detected that the thickness of the second layer of film was within 2.05 um, it had been rotating at 3000 rpm for 17 seconds, and the speed was adjusted to 1000 rpm. After maintaining for 15 seconds, it dropped to a stationary state. During the process, the quartz substrate was washed on the edge and the back was cleaned. The quartz substrate was placed in an oven and baked at 100 ° C for 25 minutes. After drying to room temperature, the average thickness of the second layer of film was detected to be 2.01 um.

[0046] The film thickness distribution in this embodiment is measured and the following is obtained: Figure 1-Figure 3 The film thickness distribution measurement curve shown in the figure shows that the second film layer has a complementary effect on the first film layer, so that the entire film is more flat.

[0047] Embodiment 2:

[0048] Take a Φ50mm quartz plate and use the above process to perform glue leveling. Set the thickness of the first layer of glue film to 0.85um, the thickness of the second layer of glue film to 1.5um, and the allowable error to 5%. When leveling glue for the first time, add 5ml of photoresist, first accelerate to 4500rpm, keep for 5s, reduce the speed to 3000rpm within 1s, keep for 5s, detect that the thickness of the first layer of glue film on the quartz substrate is 1.14um, accelerate to 4500rpm within 1s, keep for 5s, reduce the speed to 3000rpm within 1s, detect that the thickness of the first layer of glue film on the quartz substrate is 0.97um, accelerate to 3907rpm, maintained for 5s, reduced speed to 3000rpm within 1s, detected thickness of the first layer of film on the quartz substrate was 0.91um, accelerated to 3438rpm within 1s, maintained for 5s, reduced speed to 3000rpm within 1s, detected thickness of the first layer of film on the quartz substrate was 0.86um, controlled speed reduced to 1000rpm, maintained for 15s and then reduced to static state, during which the quartz substrate was washed on the edge and back, placed in an oven at 90℃, baked for 20min, dried to room temperature, detected average thickness of the first layer of film was 0.83um.

[0049] When the second glue was evenly applied, 5 ml of photoresist was added, and the speed was accelerated to 2000 rpm within 3 seconds and maintained for 10 seconds. During the process, the exhaust was vertically exhausted to the glue dripping range of the quartz substrate, and the exhaust pressure was 100 Pa. The speed was accelerated to 3000 rpm within 3 seconds, and the exhaust was vertically and evenly exhausted to the entire upper surface of the quartz substrate, and the exhaust pressure was 100 Pa. When it was detected that the thickness of the second layer of film was within 1.58 um, it had been rotating at 3000 rpm for 26 seconds, and the speed was adjusted to 1000 rpm. After maintaining for 15 seconds, it dropped to a stationary state. During the process, the quartz substrate was washed on the edge and the back was cleaned. The quartz substrate was placed in an oven and baked at 100°C for 25 minutes. After drying to room temperature, the average thickness of the second layer of film was detected to be 1.54 um.

[0050] Embodiment three:

[0051] Take a Φ50mm quartz plate and use the above process to perform glue leveling. Set the thickness of the first layer of glue film to 1.1um, the thickness of the second layer of glue film to 1.8um, and the allowable error to 5%. When leveling glue for the first time, add 6ml of photoresist, first accelerate to 4500rpm, keep for 5s, reduce speed to 3000rpm within 1s, and keep for 5s. The thickness of the first layer of glue film on the quartz substrate is detected to be 1.23um. Accelerate to 3751rpm within 1s, keep for 5s, reduce speed to 3000rpm within 1s, and check The thickness of the first layer of film on the quartz substrate was measured to be 1.17um. The speed was accelerated to 3394rpm within 1s and maintained for 5s. The speed was reduced to 3000rpm within 1s and the thickness of the first layer of film on the quartz substrate was detected to be 1.12um. The speed was controlled to be reduced to 1000rpm and maintained for 15s before being reduced to a stationary state. During the process, the edges and back of the quartz substrate were washed and the quartz substrate was placed in an oven at 90℃ for 20min. After drying to room temperature, the average thickness of the first layer of film was detected to be 1.09um.

[0052] When the second glue was evenly applied, 5 ml of photoresist was added, and the speed was accelerated to 2000 rpm within 3 seconds and maintained for 10 seconds. During the process, the exhaust was vertically exhausted to the glue dripping range of the quartz substrate, and the exhaust pressure was 100 Pa. The speed was accelerated to 3000 rpm within 3 seconds, and the exhaust was vertically and evenly exhausted to the entire upper surface of the quartz substrate, and the exhaust pressure was 120 Pa. When it was detected that the thickness of the second layer of film was within 1.89 um, it had been rotating at 3000 rpm for 21 seconds, and the speed was adjusted to 1000 rpm. After maintaining for 15 seconds, it dropped to a stationary state. During the process, the quartz substrate was washed on the edge and the back was cleaned. The quartz substrate was placed in an oven and baked at 100 ° C for 25 minutes. After drying to room temperature, the average thickness of the second layer of film was detected to be 1.85 um.

[0053] The quartz plate adhesive films obtained in the above examples are summarized to obtain the following data table:

[0054]

[0055] It can be concluded from the above table that the error of the films processed by this process is within 5%, and both the first layer of film and the second layer of film are controllable.

[0056] In summary, the quartz substrate is coated with glue twice. In the first coating, the first stage variable speed glue leveling is adopted, which can quickly level the photoresist on the quartz substrate and prevent the appearance of reticulation on the edge of the quartz substrate, thereby ensuring the flatness and uniformity of the first layer of glue film on the quartz substrate. The thickness of the first layer of glue film is detected by an infrared micrometer, and the rotation speed is calculated and set according to the detected thickness of the first layer of glue film. The speed is adjusted for different quartz substrates in a targeted manner to ensure that the error range of the film thickness is within 5%. When the thickness of the first layer of glue film is ensured to be within the set range, the second layer of glue film is coated on the basis of the first layer of glue film. The glue leveling speed of the second layer of glue film is slower. At this time, the second layer of glue film is pressurized with an air pressure of 100Pa-120Pa to ensure that the overall surface is smoother on the basis of the thick film layer, thereby achieving the uniformity of the entire film layer.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A photolithography coating process with controllable coating thickness for producing quartz substrates, characterized in that: The following steps are involved: S1: The quartz substrate is pre-treated and adsorbed onto the vacuum chuck; S2: Control the rotation of the quartz substrate, drip photoresist to the center of the quartz substrate, rotate it at a variable speed within a set time period, measure whether the film thickness is within the set range, clean the back side and dry it. The specific steps are as follows: S21: Control the quartz substrate to accelerate to 1000 rpm within 1 second, drip photoresist onto the quartz substrate, adopt the first stage variable speed glue spreading, and detect the thickness of the first glue film at the same time. The specific process of the first stage variable speed glue spreading is as follows: first accelerate to 4500 rpm, maintain for 5 seconds, decelerate to 3000 rpm within 1 second, and maintain for 5 seconds. When the speed is 3000 rpm, detect the first glue film of the quartz substrate. If the error range of the film thickness is outside 25%, perform the previous acceleration and deceleration again. If the error range of the film thickness is within 25%, enter the second stage variable speed glue spreading. S22: Use the second stage variable speed glue spreading to detect the thickness of the first glue film and control the glue film thickness to within the set range. The specific process of the second stage variable speed glue spreading is as follows: accelerate to the set speed within 1s, maintain for 5s, reduce the speed to 3000 rpm, maintain for 5s, and then perform 1-4 times of acceleration to the set speed and reduction to 3000 rpm. When the speed is 3000 rpm, the thickness of the first layer of glue film on the quartz substrate is detected. When the error range between the detected film thickness and the set film thickness is within 5%, stop the second stage speed change. The set speed is calculated according to the detected thickness of the first layer of glue film. The calculation formula of the set speed is: V2 = 3000 (T1·T1) / (T2·T2), where V2 is the set speed, T1 is the current film thickness, and T2 is the set film thickness. S23: Control the speed to drop to 1000 rpm, maintain for 15 seconds and then drop to a stationary state. During this process, wash the edge and back of the quartz substrate, place the quartz substrate in an oven, and bake at 90°C for 20 minutes. S3: The quartz substrate is adsorbed onto the vacuum chuck again, and photoresist is dripped onto the center of the quartz substrate. The substrate is first rotated at the first speed and then at the second speed. The thickness is controlled by exhaust pressure. The back side is cleaned and then dried.

2. The photolithography coating process with controllable coating thickness for producing quartz substrates according to claim 1, characterized in that: The pretreatment process of the quartz substrate in S1 is as follows: the quartz substrate to be coated with glue is cleaned, the cleaning water is blown off, and then it is dried to check if there is no water mark, the quartz substrate is adsorbed onto a vacuum suction cup, a diluent is dripped onto the quartz substrate, and it is shaken evenly.

3. The photolithography coating process with controllable coating thickness for producing quartz substrates according to claim 2, characterized in that: The specific steps of S3 are as follows: S31: drip photoresist onto the center of the quartz substrate, accelerate to 2000 rpm within 3 seconds, and maintain for 10 seconds. During this process, exhaust the gas vertically toward the dripping range of the quartz substrate; S32: accelerate to 3000 rpm within 3 seconds. During this process, vertically and uniformly exhaust gas to the entire upper surface of the quartz substrate, and monitor the thickness of the second layer of film on the quartz substrate at the same time; S33: When the thickness of the second layer of film on the quartz substrate reaches the set value, the rotation speed is controlled to drop to 1000 rpm, maintained for 15 seconds and then dropped to a stationary state. During the process, the quartz substrate is washed on the edge and the back, and the quartz substrate is placed in an oven at 100°C for 25 minutes.

4. The photolithography coating process with controllable coating thickness for producing quartz substrates according to claim 3, characterized in that: The exhaust pressure is 100Pa-120Pa.

5. The photolithography coating process with controllable coating thickness for producing quartz substrates according to claim 4, characterized in that: The thickness of the first layer of adhesive film and the second layer of adhesive film are measured by an infrared micrometer.

Citation Information

Patent Citations

  • Method for controlling thickness of coating on wafer

    CN113851370A

  • High-precision quartz substrate glue and production process thereof

    CN115793397A

  • Wafer gluing method

    CN116068857A